Proving Woman : Female Spirituality and Inquisitional Culture in the Later Middle Ages - Elliott, Dyan, 1954- (Book collections on Project MUSE., 2014)
Around the year 1215, female mystics and their sacramental devotion were among orthodoxy's most sophisticated weapons in the fight against heresy. Holy women's claims to be in direct communication with God placed them in positions of unprecedented influence. Yet by the end of the Middle Ages female mystics were frequently mistrusted, derided, and in danger of their lives. The witch hunts were just around the corner. While studies of sanctity and heresy tend to be undertaken separately, Proving Woman brings these two avenues of inquiry together by associating the downward trajectory of holy women with medieval society's progressive reliance on the inquisitional procedure. Inquisition was soon used for resolving most questions of proof. It was employed for distinguishing saints and heretics; it underwrote the new emphasis on confession in both sacramental and judicial spheres; and it heralded the reintroduction of torture as a mechanism for extracting proof through confession. As women were progressively subjected to this screening, they became ensnared in the interlocking web of proofs. No aspect of female spirituality remained untouched. Since inquisition determined the need for tangible proofs, it even may have fostered the kind of excruciating illnesses and extraordinary bodily changes associated with female spirituality. In turn, the physical suffering of holy women became tacit support for all kinds of earthly suffering, even validating temporal mechanisms of justice in their most aggressive forms. The widespread adoption of inquisitional mechanisms for assessing female spirituality eventuated in a growing confusion between the saintly and heretical and the ultimate criminalization of female religious expression.